Invasive procedures in the outpatient setting: Managing the short-acting acenocoumarol and the long-acting phenprocoumon - van Geest-Daalderop, Johanna H. H.; Hutten, Barbara A.; Péquériaux, Nathalie C. V.; de Vries-Goldschmeding, Hanneke J.; Räkers, Emmy; Levi, Marcel (Thrombosis and Haemostasis, 2007)
Treatment with vitamin K antagonists (VKAs) has to be interrupted when invasive procedures are planned. We compared various methods of interruption in patients on acenocoumarol or phenprocoumon in a prospective study. In patients on acenocoumarol (n=141), 99 stopped three days before the intervention and 42 stopped two days before. All patients on phenprocoumon (n=111) received vitamin K two days before the intervention, and 55 of these patients discontinued phenprocoumon, whereas 56 did not stop. In a subset of 30 patients we determined International Normalized Ratios (INRs) and coagulation factors II,VII, X and protein C. The mean INR after stopping acenocoumarol for three days was significantly lower than after two days (1.1 vs. 1.3, p=<0.0001), but its clinical relevance may be trivial. In patients using phenprocoumon, the mean INR on the day of the intervention was only slightly lower after stopping the VKAs (1.5 vs. 1.6, p=0.0407), but a similar proportion of patients had an INR ≤1.4. On the day of the intervention, in the acenocoumarol group mean plasma levels of all coagulation factors were higher than 50% and in the phenprocoumon group higher than 25%. We conclude that acenocoumarol can be stopped two days before an invasive procedure that is associated with a low or moderate bleeding risk and three days before an intervention with a higher bleeding risk. For phenprocoumon, administration of vitamin K two days before an intervention results in an acceptable INR during the intervention, regardless whether phenprocoumon is interrupted or not.
Keywords: Acenocoumarol; phenprocoumon; invasive procedures; coagulation factors